Sticky Feet: How Labor Market Frictions Shape the Impact of International Trade on Jobs and Wages - Hollweg, ClaireH. (World Bank, 2015)
The analysis in this report confirms the findings of previous studies that trade liberalization improves aggregate welfare and is in the long run associated with higher employment and wages. The analysis addresses a major gap in the literature, which has heretofore provided limited evidence about the trade-related adjustment costs faced by workers in developing countries and how they are affected by mobility costs.